Assessing the Variations of the Depth and Angle of the Submandibular Gland Fossa and the Mandibular Canal Using Cone Beam Computed Tomography (CBCT): Submandibular Gland Fossa assessment using CBCT - Khodabakhshian, Alireza; Mollaei, Melika; Alimohammadi, Mona; Ghobadi, Fatemeh; Hosseinnataj, Abolfazl; Gholampour, Atefeh (Regeneration, Reconstruction & Restoration (Triple R), 2024)
Background and objectives: The most important anatomical areas to take into account during implant insertion are the submandibular gland cavity, the posterior part of the mandible, and the inferior alveolar nerve. Therefore, this study aims to assess the location of the submandibular gland fossa and its variations using CBCT. Materials and methods: In this cross-sectional investigation, CBCT images of the mandible of patients who visited a private radiology center in Babol (Mazandaran, Iran) between 2019 and 2021 were included. The submandibular salivary gland fossa was evaluated based on age, sex, side of the mandible, fossa depth and angle, as well as connection with the mental foramen and mandibular canal. Data were analyzed using SPSS V.24. Results: The study population comprised 59 men (47.2%) and 66 (52.8%) women, ranging from 16 to 70 years old. The mean depth of the fossa on the right side (1.79 ± 0.48 mm) was statistically greater than the left side (1.66 ± 0.46 mm). Regarding the angle of the fossa and the distance to the mental foramen, there was no discernible difference between the left and right sides. Men had considerably deeper average fossa depths on both sides (P<0.05). Moreover, the fossa depth on the right side was significantly lower in patients less than 36 years old (P=0.005). Conclusion: According to the current findings, the average depth of the fossa is greater on the right side than on the left side. The deepest part of the fossa is located next to the mandibular canal. Therefore, it is crucial to have a thorough understanding of the characteristics of the submandibular gland fossa to avoid perforating the lingual alveolar plate during implant insertion. Keywords: Cone Beam Computed Tomography, CBCT, Dental implant, Submandibular gland fossa.